The course of plasma cortisol concentration after three different doses of ketamine in xylazine-premedicated calves. (May 2019) - Steckeler, Patricia; Fux, Daniela; Metzner, Moritz; Knubben, Gabriela; Rieger, Anna; Baumgartner, Christine
Abstract: Objective: To investigate the influence of ketamine on plasma cortisol concentration (PCC) in calves. Study design: Prospective, randomized experimental study. Animals: A total of 41 healthy, predominantly cross-bred calves, aged 3–4 months. Methods: Calves were premedicated with intramuscular xylazine (0.2 mg kg –1 ) and randomly divided into four groups. The control group (CONT) received saline (after 10, 20 and 30 minutes), whereas groups K1, K2 and K3 were injected intravenously once, twice or thrice, respectively, with 4 mg kg –1 of ketamine at 10 minute intervals. Blood samples were collected at fixed time points and analysed to determine the PCC; furthermore, the plasma concentrations of ketamine and norketamine were assessed after a single ketamine administration in group K1. The pharmacokinetic parameters of ketamine and norketamine were calculated as plasma concentrations versus time. Results: All groups showed significant ( p < 0.0001) increases in PCC compared with the baseline value; however, for the first 60 minutes, PCC was significantly higher in the ketamine-treated groups (time × dose effect; K1: p < 0.0001; K2: p = 0.0008; K3: p = 0.0135) than in the CONT group. The group receiving triple ketamine administration exhibited the greatest increase in PCC compared with the baseline level (121.17 ± 33.25 nmol L –1 ), whereas in the CONT group, the increase in PCC was smaller than the baseline cortisol level (82.67 ± 36.86 nmol L –1 ). The plasma concentration of ketamine decreased with a half-life of approximately 12 minutes, which was longer than the dose interval. The increase in PCC after triplicate administration might, therefore, have resulted from ketamine/norketamine accumulation rather than from the total dosage. Conclusions and clinical relevance: Our results showed that ketamine increases the plasma concentration of cortisol in xylazine-treated calves. Thus, the previous treatment of subjects needs to be considered in studies using plasma/serum cortisol concentrations as an indicator of pain.